Hope for a tender sprig : Jehoiachin in biblical theology - Patton, Matthew H. (Winona Lake, Indiana : Eisenbrauns, 2016)
"Jehoiachin reigned a mere three months before Nebuchadnezzar took him into exile. He was one more Judean king who did evil in the eyes of Yahweh, and his one recorded action as king was to surrender to the Babylonians. The significance of his reign became the focus of ongoing prophetic discussion about the monarchy, his rehabilitation by Evil-Merodach was a turning point in the exile, and his offspring was eventually identified as the future of David's line. The attention paid to Jehoiachin in the canon is the seed of Patton's study. The exile was one of the most significant events in the history of Israel. In its midst, Jehoiachin occupies an important position as both one of the last kings of Judah and one of the first exiles"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Jehoiachin, -- King of Judah -- Biblical teaching; Bible. -- Theology; Bible. -- Criticism, interpretation, etc; Jehoiachin, -- King of Judah; Bible; Biblical teaching; Theology; RELIGION / Biblical Studies / Old Testament; Criticism, interpretation, etc; Electronic books